PELATIHAN PENGELOLAAN KEUANGAN PADA BANK SAMPAH MUTIARA KELURAHAN TUAH KARYA KECAMATAN TUAH MADANI KOTA PEKANBARU - Arini; Novianti, Serly; Fithrie, Souvya (UIR Press, 2026)
This community service activity aims to provide knowledge about proper and effective basic financial management tailored to the needs of our partner, the Mutiara Waste Bank in Tuah Karya Village, Tuah Madani Subdistrict, Pekanbaru City. The activity employs a hands-on, face-to-face approach by conducting training on financial management for the Mutiara Waste Bank in Tuah Karya Village, Tuah Madani Subdistrict, Pekanbaru City. A waste bank is a facility used to collect pre-sorted waste. By depositing waste at the waste bank, value is generated, thereby providing additional benefits to the surrounding community. By depositing waste that holds “value” at the waste bank—which is then managed by the bank—additional income is generated for the community. The hope for this community service initiative is to provide solutions for the Mutiara Waste Bank in managing its finances, thereby fostering financial transparency. Furthermore, it aims to create a clean, healthy, and productive living environment in the Tuah Madani Village area, which will enhance the economic value for its residents.